# PEMDAS RULE WORKSHEET

Click here to learn PEMDAS Rule in detail.

Question 1 :

Evaluate :

47 - 12 x 3

Question 2 :

Evaluate :

5 + (21 - 32÷ 4

Question 3 :

Evaluate :

11 x 7 - 30 ÷ 5

Question 4 :

Evaluate :

84 ÷ [(18 - 16) x 3]

Question 5 :

Evaluate :

3 + 2(25 + 15 ÷ 3 x 7 - 3 x 8) - 12

Question 6 :

Evaluate :

(23 + 8) ÷ 8 x (96 ÷ 12)

Question 7 :

Evaluate :

(84 ÷ 14)2 + 2 x (12 - 8)

Question 8 :

Evaluate :

7 + [43 - 3(12 - 7)] ÷ 22

Question 9 :

Evaluate :

2(30 ÷ 6)2 ÷ 5 + 3(15 + 11) ÷ 13

Question 10 :

Evaluate :

0.5(20 + 23) ÷ 7 + 2 x 6 - 5

Question 11 :

Evaluate :

(54 ÷ 52) ÷ 52 x 52

Question 12 :

Evaluate :

ab- (a + c) ÷ a + (a + b)

if a = 4, b = 6 and c = 8.

Question 13 :

Evaluate the following expression for x = -1 and y = 2 :

x+ 3y3

Question 14 :

Evaluate the following expression for x = 1 and y = 1.

(y3 + x) ÷ 2 + x

Question 15 :

Evaluate the following expression for y = 3 and z = 7.

z3 - (y ÷ 3 - 1)

Question 16 :

Evaluate :

Question 17 :

Evaluate :

Question 18 :

Evaluate :

Question 19 :

What is the value of

if a = -1/2, b = 3/2 and c = 5/2?

Question 20 :

What is the value of

if p = 4, q = 1/2 and r = 2?

47 - 12 x 3

 OperationMultiplySubtractResult Evaluation= 47 - 12 x 3= 47 - 36= 11

5 + (21 - 32) ÷ 4

 OperationExponent2ParenthesesDivideAddResult Evaluation= 5 + (21 - 32) ÷ 4= 5 + (21 - 9) ÷ 4= 5 + 12 ÷ 4= 5 + 3= 8

11 x 7 - 30 ÷ 5

 OperationMultiplyDivideSubtractResult Evaluation= 11 x 7 - 30 ÷ 5= 77 - 30 ÷ 5= 77 - 6= 71

84 ÷ [(18 - 16) x 3]

 OperationBracketsParenthesesBracketsDivideResult Evaluation= 84 ÷ [(18 - 16) x 3]= 84 ÷ [(18 - 16) x 3]= 84 ÷ [2 x 3]= 84 ÷ 6= 14

3 + 2(25 + 15 ÷ 3 x 7 - 3 x 8) - 12

 OperationParenthesesDivideMultiplyAddParenthesesMultiplyAddSubtractResult Evaluation= 3 + 2(25 + 15 ÷ 3 x 7 - 3 x 8) - 12= 3 + 2(25 + 15 ÷ 3 x 7 - 3 x 8) - 12= 3 + 2(25 + 5 x 7 - 3 x 8) - 12= 3 + 2(25 + 35 - 24) - 12= 3 + 2(60 -  24) - 12= 3 + 2(36) - 12= 3 + 72 - 12= 75 - 12= 63

(23 + 8) ÷ 8 x (96 ÷ 12)

 OperationParenthesesExponentParenthesesDivideMultiplyResult Evaluation= (23 + 8) ÷ 8 x (96 ÷ 12)= (23 + 8) ÷ 8 x 8= (8 + 8) ÷ 8 x 8= 16 ÷ 8 x 8= 2 x 8= 16

(84 ÷ 14)2 + 2 x (12 - 8)

 OperationParenthesesExponentMultiplyAddResult Evaluation= (84 ÷ 14)2 + 2 x (12 - 8)= 62 + 2 x 4= 36 + 2 x 4= 36 + 8= 44

7 + [43 - 3(12 - 7)] ÷ 22

 OperationBrackets2Parentheses2Multiply2BracketsExponent2DivideAddResult Evaluation= 7 + [43 - 3(12 - 7)] ÷ 22 = 7 + [43 - 3(12 - 7)] ÷ 22 = 7 + [43 - 3(5)] ÷ 22= 7 + [43 - 15] ÷ 22= 7 + 28 ÷ 22= 7 + 28 ÷ 4= 7 + 7= 14

2(30 ÷ 6)2 ÷ 5 + 3(15 + 11) ÷ 13

 OperationParentheses2ExponentMultiplyDivideAddResult Evaluation= 2(30 ÷ 6)2 ÷ 5 + 3(15 + 11) ÷ 13 = 2(5)2 ÷ 5 + 3(26) ÷ 13= 2(25) ÷ 5 + 3(26) ÷ 13= 50 ÷ 5 + 78 ÷ 13= 10 + 6= 16

0.5(20 + 23÷ 7 + 2 x 6 - 5

 OperationParentheses2Exponent2ParenthesesMultiplyDivideMultiplyAddSubtractResult Evaluation= 0.5(20 + 23) ÷ 7 + 2 x 6 - 5= 0.5(20 + 23) ÷ 7 + 2 x 6 - 5= 0.5(20 + 8) ÷ 7 + 2 x 6 - 5= 0.5(28) ÷ 7 + 2 x 6 - 5= 14 ÷ 7 + 2 x 6 - 5= 2 + 2 x 6 - 5= 2 + 12 - 5= 14 - 5= 9

(54 ÷ 52) ÷ 52 x 52

 OperationParentheses2Exponents2ParenthesesExponent2Exponent2MultiplyMultiplyResult Evaluation= (54 ÷ 52) ÷ 52 x 52= (54 ÷ 52) ÷ 52 x 52= (625 ÷ 25) ÷ 52 x 52= 25 ÷ 52 x 52= 25 ÷ 25 x 52= 25 ÷ 25 x 25= 1 x 25= 25

ab- (a + c) ÷ a + (a + b)

Substitute a = 4, b = 6 and c = 8.

4(6)- (4 + 8) ÷ 4 + (4 + 6)

 OperationParentheses2Exponent2MultiplyDivideSubtractionAddResult Evaluation= 4(6)2 - (4 + 8) ÷ 4 + (4 + 6)= 4(6)2 - 12 ÷ 4 + 10= 4(36) - 12 ÷ 4 + 10= 144 - 12 ÷ 4 + 10= 144 - 3 + 10= 141 + 10= 151

= x+ 3y3

Substitute x = -1 and y = 2.

= (-1)+ 3(2)2

Evaluation :

 ExponentMultiplicationAdditionResult = (-1)2 + 3(2)2= 1 + 3(4)= 1 + 12= 13

= (y3 + x) ÷ 2 + x

Substitute x = 1 and y = 1.

= (13 + 1) ÷ 2 + 1

Evaluation :

 Parentheses1ExponentParenthesesDivisionAdditionResult = (13 + 1) ÷ 2 + 1= (13 + 1) ÷ 2 + 1= (1 + 1) ÷ 2 + 1= 2 ÷ 2 + 1= 1 + 1= 2

= z3 - (y ÷ 3 - 1)

Substitute y = 3 and z = 7.

= 73 - (3 ÷ 3 - 1)

Evaluation :

 1Parentheses1Division1Subtraction1ExponentResult = 73 - (3 ÷ 3 - 1)= 73 - (3 ÷ 3 - 1)= 73 - (1 - 1)= 73 - 0= 243

if a = -1/2, b = 3/2 and c = 5/2?

if p = 4, q = 1/2 and r = 2?

Click here to get step by step answers for the above questions.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

## Recent Articles

1. ### Order of Operations Worksheet

Jul 24, 24 03:02 AM

Order of Operations Worksheet

2. ### Order of Operations

Jul 24, 24 03:01 AM

Order of Operations - Concept - Solved Examples

3. ### PEMDAS Rule Worksheet

Jul 24, 24 02:50 AM

PEMDAS Rule Worksheet